THE IMPACT OF ARTIFICIAL INTELLIGENCE ON CREATIVE WRITING: IS IT BENEFICIAL OR DETRIMENTAL DEVELOPMENT? - Suma Priyadarshini. B. K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
AI, despite its inherent limitations, is a versatile tool for writing and creative writing. I firmly believe that the human brain is unparalleled, as all human inventions are products of its ideas and thoughts. Hence, the creation of inventions in any domain can improve and benefit humanity. Therefore, technologies like artificial intelligence (AI) aim to enhance writing skills in general, particularly when it comes to creative writing too. AI functions by recognising and reproducing patterns in data, including language, in the context of AI-generated fiction. Creativity has always been associated with human cognition and intuition, resulting in novel and distinct results. Creative writing aims to captivate, enlighten, and inspire its audience, whether through written or spoken mediums. As writers utilize technologies to aid in the writing process, they encounter a set of questions that revolve around important features resulting from their partnership with artificial intelligence, namely about authenticity and originality. The concept of originality, which arises from a writer’s creative abilities, has historically been within the domain of the human intellect.